Concepções de professores e o livro didático : o ensino de divisão nos anos iniciais do ensino fundamental - Paz, Peterson da (2013)
In this paper we seek to answer the following question: What conceptions of teaching and learning of mathematics teachers of the early years of elementary school teaching reveal the division of natural numbers and what relationships are established between these concepts and the approach of this content in the textbooks adopted in their classes? Considering the nature of this research, the research methodology adopted was a qualitative interpretative approach, in which we have considered in Bogdan and Biklen (1994), Lüdke and Andrew (1986) among others. The research was conducted in the context of a public school of the state of Mato Grosso participant in “Projeto Observatório da Educação com foco em Matemática e Iniciação às Ciências”2 . The subjects were two teachers who work in the fourth year of elementary school. Used in the production of information for analyzing open- ended questionnaires, structured interviews, classroom observation, field notebook and desk review of some books available for students and teachers adopted the textbook in their classes. Due to the intention of stop us in a specific context (a school) and seek a greater understanding of the concepts of only two subjects, we believe that this research approach a case study. Through our theoretical construct, which was about the philosophical views in relation to mathematical knowledge, perspectives epistemological and pedagogical trends over time were set up in Brazil, we chose to analyze and interpret information from two basic categories, the Traditional Design Education Mathematics and Mathematics Education in Contemporary Design. We base not in the attempt to frame the subject, nor the textbooks examined, in either category, because hardly perceive the subject glaringly these conceptions, but to seek approximations with them. In response to the research question, we believe, the information produced, the subjects' conceptions move between both perspectives we elect as categories of analysis, but with a strong tendency to Traditional Design for Teaching Mathematics. Regarding textbooks examined, we see closer to Design Contemporary Mathematics Education. In general, the approach of textbooks, ie, the view expressed in textbooks, did not influence significantly the way the teachers treated the division of natural numbers. Elements from their experiences as students of basic education are much more present in their practices. Still, it is possible to realize the strong presence of the book in the classroom. It serves not only north of the student, but also for the teacher, both in curricular as well as methodological aspects.